2018
DOI: 10.1088/1361-6463/aaa992
|View full text |Cite
|
Sign up to set email alerts
|

Clustered vacancies in ZnO: chemical aspects and consequences on physical properties

Abstract: Chemical nature of point defects, their segregation, cluster or complex formation in ZnO is an important area of investigation. In this report, 1.2 MeV Ar ion beam is used to incorporate defects in granular ZnO. Evolution of defective state with irradiation fluence 1 × 10 14 and 1 × 10 16 ions/cm 2 has been monitored using x-ray photoelectron spectroscopy (XPS), photoluminescence (PL) and Raman spectroscopic study. Choice of such fluence regime ensures spatial overlapping of successive ion-target collision cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 88 publications
0
32
0
Order By: Relevance
“…It is facilitated by the chemisorbed oxygen atom and lattice oxygen in nanocomposites [34]. As shown in Figure 2(d), the bounding energy locations of 1045.5 eV and 1021.7 eV conform to the present of two atomic states, Zn2p 1/2 and Zn2p 3/2 corresponding to the electronic configuration of Zn 2+ [35].…”
Section: Component Analysismentioning
confidence: 79%
“…It is facilitated by the chemisorbed oxygen atom and lattice oxygen in nanocomposites [34]. As shown in Figure 2(d), the bounding energy locations of 1045.5 eV and 1021.7 eV conform to the present of two atomic states, Zn2p 1/2 and Zn2p 3/2 corresponding to the electronic configuration of Zn 2+ [35].…”
Section: Component Analysismentioning
confidence: 79%
“…It is to be mentioned that the variation in PL with fluence is not so systematic like Raman results. In the current context, one reason could be that the probing depth of PL and Raman is different . Additional effects like sputtering (during implantation), presence of gaseous O 2 and N 2 (during annealing) can alter the near‐surface region in a different way compared with the bulk.…”
Section: Resultsmentioning
confidence: 99%
“…The first two emissions are FX and DBX emissions of ZnO. This DBX emission is generally originated from I Zn type of native defects . The most intense PL peak at 3.313 eV is the famous FA (free electron to shallow but localized acceptors) transition in ZnO .…”
Section: Resultsmentioning
confidence: 99%
“…[11] In contrast, severalr ecent studies and calculations hint at the relevance of multiple defects, in which clustering and/or pairing occurs andl eads to increased stability. [16] It has been shown that V Zn and V O appear simultaneously and remain as nearest neighbors, either as divacancies V Zn -V O or as vacancy clusters V Zn -(V O ) n . [17] Recently,d ensity functional calculations also predicted strong interactions between V O and Zn i sites.…”
Section: Introductionmentioning
confidence: 99%